Job Satisfaction on Job Performance of Employees in Iraqi Grain Trade Companies - Ali Hassan Ezzeddine; Yasmin Ahmad; Amani Ali Elmetwaly (International Business and Accounting Research Journal, 2023)
This research article aims to â€œTo measure the impact of key predictors of job satisfaction on job performance of employees in Iraqi grain trade companiesâ€. The paper applies data reduction using Confirmatory Factor Analysis (CFA) on a sample of 745 respondents drawn from grain trade companies in the Baghdad and condenses a set of 12 job satisfaction items converted into four key predictors. The present study proposes a model of the impact of key predictors of job satisfaction on job performance. The study found that pay, supervision, work itself and promotion are impacting significantly the job performance. Therefore, grain trade companies should focus on the above factors to job performance of employees. The study investigated the impact of key predictors of job satisfaction on job performance of the employees in grain trade concluded that pay had the highest impact on the job performance of the employeesâ€™ supervision, work itself followed by promotions.